Morphological characterisation of Bambara groundnut (Vigna subterranea (L.) Verdc.) germplasm collections: A basis for crop improvement - Johanna Shekupe Valombola; Simon Kamwele Awala; Kudakwashe Hove (Journal of Agriculture and Applied Biology, 2022)
Bambara groundnut is one of the underutilised legume crops adapted to Sub-Saharan Africa's harsh, semi-arid tropical regions, providing nutrition and cash income among resource-poor farmers. A field study comprising 25 Bambara groundnut accessions was carried out during the 2018/2019 cropping season at the Crop Science Experimental Field, University of Namibia-Ogongo Campus, to characterise the accessions using qualitative traits. The experimental design used was an alpha lattice with three replications. Based on the visual observation techniques, the results showed morphological variation among the genotypes. The Bambara groundnut germplasm studied showed high phenotypic variations. The germplasm had a high proportion of the bunch-type growth habit (44% accessions), oval leaflet shape (64%), sparse hairiness (56%), and absence of eye pattern colour (70%). Also, cluster analysis grouped the accessions into five super classes. Shanon-Wennier index indicated a significant level of diversity among the Bambara groundnut accessions for most traits studied, with plant growth habits having the highest index of 2.15, followed by for pod colour (1.45) and seed eye pattern colour (1.22). These results may be useful in formulating national Bambara groundnut breeding programs in semi-arid Sub-Saharan African regions. However, molecular analysis is required to determine the genetic variations among the accessions.